The Linguostylistic Characteristics of the Prose of Serâğol’ Qolüb by Qatt an Ğaznawī - Karahalilović, Namir (Prilozi za orijentalnu filologiju, 2017)
Serâğol’ qolüb is a prose work, ethical-didactic in nature, originating from the classical period of Persian literatüre. With the exception of the title, which was noted differently in numerous manuscript copies of the work, other impor- tant facts related to the author (like the period vvherein he lived, his origin, education, ete.) yet remain unrevealed. In the short introduetion, the author does not give a single piece of information about himself, nor does he mention any other of his works. In available primary historical, literary and theological sources, there are no data about the author and about this or his other works. One of important questions related to the author is the issue of the period vvherein he lived. Since there are no data about the author in the primary sour- ces from the classical period, the only way of at least approximate assessment of the stated period (and the time wherefrom the work dates) is finding evi- dence and indicators about it in the work itself. The analysis of linguostylistic characteristics of the work based on the periodization of development of Persian prose as defined in the modern Persian stylistics, represents one of the more reliable methods of such an assessment, or at least the one less bur- dened by dilemmas. Based on the analysis of the linguostylistic characteristics of the prose of Serâğo l’ qolüb, it is established that the prose shows a large number of characteristics of the first, as well as some characteristics of the second phase of development of Persian prose. Prose with such characteristics is referred to as “simple prose of higher level”. As the other works wherein characteristics of this intermediate phase of Persian prose development are found, mostly date back to the second half of the 11th century, it could, although with caution, be assumed that the work Serâğol ’ qolüb by Qattan Ghaznawī originated in the period betvveen the beginning of the second half of the llth century and the end of the first half of the 12th century.